Pyrolytic lignin from fast pyrolysis bio-oil via cold-water precipitation: Optimal separation conditions and properties - Zhang, Mingming; Wu, Hongwei (Elsevier Ltd, 2019)
The paper reports the properties of pyrolytic lignin (PL) separated from a fast pyrolysis bio-oil via cold-water precipitation under various conditions. Three different mixing methods were deployed, including magnetic stirring, high-speed homogenizing and ultrasonication. The results show that the proportion of water in the bio-oil/water mixture plays a significant role in achieving complete bio-oil separation for PL production. In systems with a low water proportion (85%, corresponding to added-water/bio-oil ratio of 4), incomplete separation occurs regardless the stirring conditions. In systems with 95% water (corresponding to added-water/bio-oil ratio of 17), continuous magnetic stirring at a low speed after bio-oil addition (e.g. 750 rpm for 1 h) can be an alternative method to high-speed homogenizing (at 6000 rpm) or even repeated washing process for complete bio-oil separation for PL preparation. The PL samples prepared from these complete separation processes have similar properties in terms of elemental compositions and aromatic structure etc. For the PL samples prepared from incomplete separation in systems with a low water proportion (85%), the PL samples mostly remain in the container and are in a sticky gummy form. Compared to the powder-like PL obtained on filter paper from complete separation, those sticky PL samples have higher yields, lower molecular weights, lower carbon contents and less condensed aromatic ring structures.